التلوث والخواء الفكري لدى طلبة الجامعة من ذوي الشخصية أحادية العقلية - ناصر، حسين ناصر (جامعة بابل, 2019)
هدف البحث إلى التعرف على التلوث والخواء الفكري لدى طلبة الجامعة من ذوي الشخصية أحادية العقلية، ومعرفة الفروق في متغيرات البحث تبعا لمتغيري: الجنس (ذكور-إناث)، التخصص الدراسي (علمي-إنساني)، ومدى إسهام التلوث والخواء الفكري في الشخصية أحادية العقلية، وتألفت عينة البحث من (400) طالب وطالبة، للعام الدراسي (2017-2018)، وتم تطبيق مقياس التلوث الفكري المكون من (28) فقرة، ومقياس الخواء الفكري المتضمن (26) فقرة ومقياس الشخصية أحادية العقلية الذي تضمن (34) فقرة (إعداد الباحث)، وقد كشفت نتائج البحث عن وجود تلوث وخواء فكري وشخصية أحادية العقلية بدرجات متفاوتة لدى طلبة الجامعة، مع انعدام الفروق ذات الدلالة الإحصائية في التلوث الفكري والخواء الفكري والشخصية أحادية العقلية تبعا لمتغيري: الجنس (ذكور، إناث)، والتخصص (علمي، إنساني)، كما توصل البحث إلى وجود علاقة ارتباطية بين التلوث الفكري والخواء الفكري والشخصية أحادية العقلية، ومساهمة التلوث والخواء الفكري في الشخصية أحادية العقلية لدى طلبة الجامعة، وبناء على هذه النتائج، وضع الباحث عددا من التوصيات والمقترحات. The aim of the study was to identify the pollution and intellectual emptiness of university students with Single Minded Personality, and to know the differences in the variables of the study according to the variables: Gender (male, female), (scientific, human) the sample of the study consisted of (400) male and female students from Al Muthanna University for the academic year 2017-2018. The measure of intellectual pollution, which consisted of (28) paragraphs, and the intellectual vacuum measure which included (26) and measurement of Single Minded Personality (34) Paragraph (preparation of the researcher),The results of the study revealed the existence of pollution and intellectual emptiness and Single Minded Personality in various degree in the university students, The study also found that there is a correlation between the two variables: gender (males, females), and the study specialization (scientific, human). Intellectual pollution and intellectual and individual intellectual emptiness, and there is a contribution to the pollution and intellectual emptiness in the Single Minded Personality of university students, and based on these results, the researcher put a number of recommendations and suggestions.
Keywords: التلوث الفكري -- الثورة التكنولوجية -- المشكلات النفسية -- طلبة الجامعات